PENGELOLAAN TRANSPORTASI PUBLIK TRANS METRO PEKANBARU OLEH DINAS PERHUBUNGAN KOTA PEKANBARU TAHUN 2023-2024 - Salmiati, Mia; ,, Hasanuddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to analyze the management of Trans Metro Pekanbaru by the Urban Transport Management Unit (UPT Pengelolaan Angkutan Perkotaan) under the Department of Transportation of Pekanbaru City through four public management functions: planning, organizing, actuating, and controlling. Public transportation plays a vital role in supporting urban mobility, yet its implementation often encounters challenges ranging from limited infrastructure to inter-agency coordination issues. This research employs a qualitative descriptive approach with data collection techniques including interviews, documentation, and field observations. The results show that in terms of planning, the UPT has developed annual operational plans and route mapping, but implementation is often hindered by budget limitations and lack of synergy among local agencies. Regarding organizing, the organizational structure is in place, but work distribution is uneven and technical task assignments are suboptimal. In the actuating aspect, the unit has made efforts to improve staff performance through routine briefings and internal evaluations, but these efforts lack continuous training and motivation systems. For controlling, supervision still relies heavily on manual systems, which hampers effective reporting and responsiveness to operational issues.The study recommends strengthening human resource capacity, digitizing supervision systems, and establishing regular coordination forums among local agencies to improve the sustainability of Trans Metro Pekanbaru services. Keywords: Trans Metro Pekanbaru, public transportation management, planning, organizing, actuating, controlling, Urban Transport Management Unit.